The Influence of Marketing Mix (4P) on Purchase Intention Student Entrepreneurial Products at SMKS Al-Ma’arif Cikande–Serang - Muhammad Iqbal Ismail; Juhaeri; Denies Susanto (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of the marketing mix (4P) product, price, place, and promotion on purchase intention student entrepreneurial products at SMKS Al-Ma’arif Cikande–Serang. The research was motivated by the need to strengthen marketing strategies in school-based entrepreneurship programs, which often face similar challenges to Micro, Small, and Medium Enterprises (MSMEs), particularly in understanding consumer behavior and implementing effective marketing strategies. The marketing mix, serves as a framework to examine how these four elements interact in shaping consumer purchase intentions. The study employed a quantitative approach using a causal research design to determine the cause-and-effect relationship between the marketing mix variables and purchase intention. Data were collected from 32 respondents who had purchased or were familiar with the student entrepreneurship products. A saturated sampling technique was used, and data analysis was performed with SPSS version 27, including validity, reliability, classical assumption, and multiple linear regression tests. The findings reveal that product and price have a significant and positive effect on purchase intention, while place and promotion show a positive but not significant effect. The regression model indicates a strong relationship between the marketing mix and purchase intention, with an R² value of 0.844, meaning that 84.4% of purchase intention can be explained by the four variables. In conclusion, improving product innovation and pricing strategies is crucial to enhancing consumer purchase intention, while expanding distribution access and digital promotion can further strengthen market engagement. This study provides valuable insights for educational institutions to integrate practical marketing strategies into entrepreneurship programs, thereby increasing the competitiveness and sustainability of student-made products.